Dynamic changes of hematological indices in oropharyngeal cancer patients treated with radiotherapy. (2nd December 2022) - Song, Yao; Cheng, Danni; Luo, Yaxin; Huang, Shaohui; Qiu, Ke; Rao, Yufang; Mao, Minzi; Pang, Wendu; Li, Junhong; Zheng, Yongbo; Zhao, Yu; Li, Yan; et al.
Abstract: Background: Hematological indices assist in predicting clinical outcomes. Objectives: To explore changes of hematological indices on oropharynx squamous cell carcinoma (OPSCC) patients received radiotherapy and their association with survival. Material and methods: The white blood cell count (WBC), absolute neutrophil count (ANC), absolute lymphocyte count (ALC), hemoglobin (Hb), platelet (Plt), albumin (Alb), neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) at baseline, 1-, 3-, 6- and 12-months follow-up were retrospectively collected. The trajectory of indices was described. A linear model with random effects was to describe indices' changing rate and trend. Univariable Cox analysis was to assess the correlation between indices and survival. Results: Of the 85 patients, WBC and ALC dropped during acute phase and gradually recovered, while NLR and PLR increased during acute phase and subsequently declined (all p  < .01). Higher absolute value of nutritional indices (Alb and Hb) was associated with better prognosis ( p  < .05). In contrast, patients with higher absolute value or upward trend of inflammatory indices (ANC, Plt, NLR and PLR) had worse survival ( p  < .05). Conclusions and significance: The short- and long-term changes of indices differed in OPSCC patients received radiotherapy, and absolute values and dynamic changes of indices had the potential to be prognostic factors.